Innovative imaging methods in heart failure: a shifting paradigm in cardiac assessment. Position statement on behalf of the Heart Failure Association of the European Society of Cardiology. (9th November 2018) - Čelutkienė, Jelena; Plymen, Carla M.; Flachskampf, Frank A.; de Boer, Rudolf A.; Grapsa, Julia; Manka, Robert; Anderson, Lisa; Garbi, Madalina; Barberis, Vassilis; Filardi, Pasquale Perrone; Gargiulo, Paola; Zamorano, Jose Luis; et al.
Abstract : Myriad advances in all fields of cardiac imaging have stimulated and reflected new understanding of cardiac performance, myocardial damage and the mechanisms of heart failure. In this paper, the Heart Failure Association assesses the potential usefulness of innovative imaging modalities in enabling more precise diagnostic and prognostic evaluation, as well as in guiding treatment strategies. Many new methods have gradually penetrated clinical practice and are on their way to becoming a part of routine evaluation. This paper focuses on myocardial deformation and three‐dimensional ultrasound imaging; stress tests for the evaluation of contractile and filling function; the progress of magnetic resonance techniques; molecular imaging and other sound innovations. The Heart Failure Association aims to highlight the ways in which paradigms have shifted in several areas of cardiac assessment. These include reassessing of the simplified concept of ejection fraction and implementation of the new parameters of cardiac performance applicable to all heart failure phenotypes; switching from two‐dimensional to more accurate and reproducible three‐dimensional ultrasound volumetric evaluation; greater tissue characterization via recently developed magnetic resonance modalities; moving from assessing cardiac function and congestion at rest to assessing it during stress; from invasive to novel non‐invasive hybrid techniques depicting coronary anatomy and myocardial perfusion; as well as from morphometry to the imaging of pathophysiologic processes such as inflammation and apoptosis. This position paper examines the specific benefits of imaging innovations for practitioners dealing with heart failure aetiology, risk stratification and monitoring, and, in addition, for scientists involved in the development of future research.